Potential Development of Retirement Village in Malaysia - Md. Yassin, Azlina; Masram, Haidaliza; Suet Khim, Ong (International Journal of Property Sciences (E-ISSN: 2229-8568), 2018)
As life styles keep changing, people are now paying more attention towards their retirement life. The decision of where to live during their retirement life is related to many factors, such as financial resources, retirement timing and health status. Retirement village is a new concept in Malaysia as compared to the developed countries and there is still lack of public knowledge and awareness towards retirement village. In Malaysia, developers have cited lack of expertise, unfamiliarity with retirement village concept and high cost as constraints faced to build and manage retirement village. Therefore, the main objective of this paper is to study an awareness of the public towards retirement village concept in Malaysia. Through a survey conducted in Ipoh, the majority of the respondents prefer to stay at their own house after retirement rather than staying at retirement village. Moreover, respondents also indicated a medium level of acceptance towards potential development of retirement village concept in Malaysia, and the provision of 24 hours security and better healthcare were identified as the prominent services to be provided for the homes. It is hoped that the findings from this study would be useful to create awareness to the relevant stakeholders comprising local governments, developer and property investors for the purpose of retirement village development in the future.